2020
DOI: 10.1111/grs.12285
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stage of maturity and lactic acid bacteria inoculants on the ensiling characteristics, aerobic stability and in vitro digestibility of whole‐crop oat silages

Abstract: This study evaluated the effect of three isolated lactic acid bacteria (LAB) inoculants on the ensiling characteristics, aerobic stability and in vitro digestibility of low dry matter whole‐crop oat silages (WCOS). The oats were harvested at two stages of maturity, boot and filling stages, and then inoculated with 1 × 106 cfu/g fresh material of Lactobacillus plantarum (LP), Lactobacillus rhamnosus (LR) and Lactobacillus buchneri (LB). After 45 days of ensiling, the three LAB inoculants increased lactic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
2
14
1
Order By: Relevance
“…As shown in Table 1 , the DM content of fresh oat was 23.70%, which was similar to the report by Jia et al and Gomes et al [ 10 , 24 ]. The contents of CP, ADF, and NDF were 13.25, 32.80 and 49.64% of DM, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As shown in Table 1 , the DM content of fresh oat was 23.70%, which was similar to the report by Jia et al and Gomes et al [ 10 , 24 ]. The contents of CP, ADF, and NDF were 13.25, 32.80 and 49.64% of DM, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Ensiling has been an important way for preserving fresh oat for a long period in the world [ 10 ]. In the last decades, the planting area of oat has expanded toward to north regions in China, where the daily mean temperature ranges from 0 °C to 15 °C.…”
Section: Introductionmentioning
confidence: 99%
“…However, lactic acid is not the only factor influencing the pH. The work of Jia et al (2020) showed that the lactic acid content and pH of oat silage made from the boot stage with a lower DM content were higher than that made from the filling stage. In the present work, HS had low DM content and high buffering capacity, more acid molecules are needed to reduce its pH value when ensiling.…”
Section: Effects Of Microbial and Chemical Factors On Fermentation Qu...mentioning
confidence: 99%
“…The work of Garnsworthy and Stokes (2009) showed that the quality of oat silage varied with its growth stages. And previous work focused more on the determination of forage chemical component changes with harvest stages (Jia et al, 2020). As another major factor affecting silage quality, the epiphytic microbial community structure of oat at different growth stages has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, significant amounts of nutrients are lost from alfalfa in the drying and storage process (Saruhan & Demirel, 2018). Production of alfalfa silage is attracting increasing attention (Jia et al, 2021), but it is difficult to ensile owing to its high protein level and buffering capacity and low water-soluble carbohydrate content. Therefore, additives must be used during ensiling.…”
Section: Introductionmentioning
confidence: 99%